Technological Innovations for Coffee Roasting: discoveries through patent analysis - Lopes, Andressa Regina (2021)
The present study aimed to characterize the 1180 patent applications for coffee roasting in the world. The technologies that could be introduced in the Brazilian industry were numerically highlighted. The results showed that the world is possibly in a cycle of growth in coffee roasting technologies. They are predominantly product innovations, are deposited primarily in a few countries, and mostly by multinationals. In conclusion, the article demonstrates that patent prospecting can be an alternative in the technological advancement of Brazilian industry and can guarantee the identification of frontier technologies in several economic sectors. The article also pointed out the need for the Brazilian Roasting & Grinding industry to analyze the 173 patents on the frontier of knowledge that have not been filed in Brazil, which can demonstrate competitive technologies and great market value. In addition, monitoring by market leaders is suggested to recognize the sector's technological trajectory.